Quarterly National Accounts Manual (2017 Edition) - Lee, Kwangwon (Manuals and Guides, 2018)
The Quarterly National Accounts Manual (the Manual) provides conceptual and practical guidance for compiling quarterly national accounts (QNA) statistics. The Manual offers a comprehensive review of data sources, statistical methods, and compilation techniques to derive official estimates of quarterly GDP. The new edition-which upgrades the first edition, published in 2001-improves and expands the previous content based on recent methodological advances, best country practices, and suggestions received from QNA compilers and experts.